Rje btsun ʼJam paʼi dbyaṅs kyi chos skor daṅ lhan thabs : a treasured collection of sādhanas focussing upon Mañjughoṣa - Dpaʼ-bo-rdo-rje, Grub-chen (Ngawang Sopa, 1977)
Rituals focussing upon a sādhana of Mañjuśrī visualized as an identity with Tsoṅ-kha-pa Blo-bzaṅ-grags-pa, founder of the Dge-lugs-pa tradition; includes.